Zeolite manufacturing method

JP2026166122APending Publication Date: 2026-10-14MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025058876
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026166122000013
    Figure 2026166122000013
  • Figure 2026166122000014
    Figure 2026166122000014
  • Figure 2026166122000015
    Figure 2026166122000015
Patent Text Reader

Abstract

This invention provides a novel method for producing zeolite with a high yield and high Al content. [Solution] A method for producing zeolite, comprising a mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor; a maturation step of maturing the aqueous reactant precursor; a raw material gel mixture preparation step of adding at least a seed crystal to obtain a raw material gel mixture; and a hydrothermal synthesis step of performing hydrothermal synthesis of the raw material gel mixture. The zeolite satisfies SiO2 / Al2O3 ≤ 13, and the seed crystal is a zeolite that has undergone de-Al treatment.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a method for producing zeolite, and more specifically, to a method for producing low Si / Al ratio zeolite inexpensively and efficiently. [Background technology]

[0002] When using zeolite catalysts as SCR catalysts for exhaust gas treatment in automobiles and other vehicles, it has been found that catalysts with a low Si / Al ratio are preferable to ensure reliable exhaust gas treatment, especially during operation at low temperatures such as during startup. This is because, in the case of aluminosilicate-based zeolites, the coordination sites of transition metals and other components that act as active sites become aluminite sites, making catalysts with a lower Si / Al ratio, which have more active sites, more advantageous.

[0003] Patent Document 1 describes a method for producing an AEI-type zeolite having a Si / Al ratio of 50 or less, comprising the steps of preparing a mixture containing silicon atom raw material, aluminum atom raw material, alkali metal atom raw material, organic structure-determining agent, and water, and hydrothermally synthesizing the mixture obtained in the first step. In the production method of Patent Document 1, the aluminum atom raw material is a compound containing aluminum with a Si content of 20% by weight or less, and the framework density in the mixture is 14T / 1000Å. 3 The description describes a method for producing AEI-type zeolite, in which the above-mentioned zeolite is included in an amount of 0.1% by weight or more relative to the SiO2, assuming that all the Si in the mixture is SiO2.

[0004] Patent Document 2 describes a method for producing AEI-type zeolite, which includes a step of hydrothermally synthesizing a mixture containing alkali metal atom raw materials, silicon atom raw materials, aluminum atom raw materials, an organic structure-regulating agent, and water, wherein the hydrothermal synthesis is carried out in a stirred-tank reactor, and the molar ratio of potassium atoms to sodium atoms in the mixture is 0.5 or more and 12 or less.

[0005] Patent Document 3 describes a method for producing AEI-type zeolite, comprising the steps of: preparing a composition containing silicon atoms, aluminum atoms, alkali metal atoms, and water; maturing the composition; adding a zeolite containing d6r, which is defined by the International Zeolite Association (IZA) as a composite building unit, in its framework after maturation; and hydrothermally synthesizing the composition after the addition of the zeolite. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2017-81809 [Patent Document 2] Japanese Patent Publication No. 2017-206417 [Patent Document 3] Japanese Patent Publication No. 2021-147260 [Overview of the project] [Problems that the invention aims to solve]

[0007] While much remains unclear about the detailed mechanism of action of seed crystals in zeolite synthesis, it is believed that zeolite crystal nuclei or precursors are generated from seed crystals dissolved (decomposed) in the raw material gel, and that zeolite is formed when these crystal nuclei or precursors grow. Therefore, seed crystals in zeolite synthesis are thought to play a role similar to that of a nucleation agent for crystals in the starting gel.

[0008] For seed crystals to function effectively, controlling their solubility is crucial. If the solubility is too low, the amount of crystal nuclei generated will be insufficient, resulting in a low crystallization-promoting effect. Conversely, if the solubility is too high, the generated crystal nuclei will dissolve rapidly, decomposing into low-molecular-weight silane oligomers and aluminosilicate oligomers, thus eliminating the crystallization-promoting effect.

[0009] Zeolite raw material gels are typically alkaline, and it is known that zeolite dissolves when added to such alkaline gels. This solubility largely depends on the amount of Al in the zeolite skeleton; zeolites with a higher Al content, i.e., zeolites with a lower Si / Al ratio, are less likely to dissolve.

[0010] AEI-type zeolites with a low Si / Al ratio, produced by the manufacturing methods described in Patent Documents 1-3, possess excellent exhaust gas treatment capabilities. However, when attempting to mass-produce them, zeolites with a low Si / Al ratio have low solubility due to their high Al content. When used as seed crystals, they generate few crystal nuclei, resulting in insufficient crystal growth promotion. Therefore, zeolites with a low Si / Al ratio are usually difficult to use as seed crystals as they are. Patent Documents 1-3 use zeolites with a high Si / Al ratio, synthesized separately from the synthesized zeolite with a low Si / Al ratio, as seed crystals. Consequently, there is room for improvement in terms of reduced production efficiency and higher costs.

[0011] If a portion of the synthesized zeolite with a low Si / Al ratio can be used directly as seed crystals for the next stage of production, it would eliminate the need to separately synthesize or procure zeolite for seed crystals, which is expected to enable more efficient and inexpensive mass production of low Si / Al ratio zeolite.

[0012] As a result of diligent research, the disclosers have found that by acid-treating the zeolite used as a seed crystal, it is possible to produce zeolite with a high Al content and good yield.

[0013] In other words, one aspect of this disclosure aims to provide a novel method for producing zeolite with a high yield and high Al content. [Means for solving the problem]

[0014] In order to solve the above problems, a method for producing a zeolite according to one aspect of the present disclosure has the configuration described below.

[0015] [1] A mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor, a ripening step of ripening the aqueous reactant precursor, a raw material gel mixture preparation step of adding at least seed crystals to obtain a raw material gel mixture, and a hydrothermal synthesis step of performing hydrothermal synthesis on the raw material gel mixture, the method for producing a zeolite, wherein the zeolite satisfies SiO₂ / Al₂O₃ ≦ 13, and the seed crystals are zeolites subjected to dealumination treatment.

[0016] [2] The method for producing a zeolite according to [1], wherein in the raw material gel mixture preparation step, an organic structure-directing agent is added to the raw material gel mixture.

[0017] [3] The method for producing a zeolite according to [1] or [2], wherein the average particle diameter of the zeolite and the seed crystals is 500 nm or less.

[0018] [4] The method for producing a zeolite according to any one of [1] to [3], wherein the seed crystals are zeolites satisfying 100>SiO₂ / Al₂O₃>13.

[0019] [5] The method for producing a zeolite according to any one of [1] to [4], wherein the dealumination treatment of the seed crystals is an acid treatment.

[0020] [6] The method for producing a zeolite according to [5], wherein the acid amount of the seed crystals after the acid treatment is 0.1 mmol / g or more and 1.6 mmol / g or less.

[0021] [7] The framework density of the zeolite and the seed crystals is 14 T / 1000 Å 3 or more and 19 T / 1000 Å 3A method for producing zeolite as described in any of the following [1] to [6].

[0022] [8] A method for producing a zeolite according to any one of [1] to [7], wherein the zeolite and the seed crystal have at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring. [Effects of the Invention]

[0023] According to one aspect of this disclosure, a novel method for producing zeolite with a high yield and high Al content can be provided. [Brief explanation of the drawing]

[0024] [Figure 1] Figure 1 is an XRD chart of the zeolite powder used to obtain seed crystals for a zeolite manufacturing method according to one embodiment of the synthesis example 1. [Figure 2] Figure 2 is a scanning electron microscope (SEM) image of zeolite powder used to obtain seed crystals for a zeolite manufacturing method according to one embodiment of the synthesis method described in Synthesis Example 1. [Figure 3] Figure 3 is an XRD chart of the zeolite powder synthesized using the seed crystal from Example 1. [Figure 4] Figure 4 is a scanning electron microscope image of the zeolite powder synthesized using the seed crystal from Example 1. [Figure 5] Figure 5 is a graph showing the catalytic activity of the Cu-containing AEI zeolite powder of Example 1. [Figure 6] Figure 6 is an XRD chart of the zeolite powder synthesized using the seed crystal of Example 2. [Figure 7] Figure 7 is a scanning electron microscope image of the zeolite powder synthesized using the seed crystal from Example 2. [Figure 8] Figure 8 is a graph showing the catalytic activity of the Cu-containing AEI zeolite powder of Example 2. [Figure 9] Figure 9 is an XRD chart of the zeolite powder synthesized using the seed crystal of Comparative Example 1. [Figure 10] Figure 10 is a scanning electron microscope image of zeolite powder synthesized using the seed crystal of Comparative Example 1. [Modes for carrying out the invention]

[0025] The embodiments of this disclosure will be described in detail below, but the following description is merely an example of the embodiments of this disclosure, and this disclosure is not limited to these. Furthermore, the embodiments of this disclosure can be combined as appropriate. In this specification, "~" means a range including the numbers described before and after it.

[0026] [Method for manufacturing zeolite] A method for producing zeolite according to one aspect of this disclosure includes a mixing step of mixing a Si element source, an Al element source, an alkali metal element source, and water to obtain an aqueous reactant precursor; a maturation step of maturing the aqueous reactant precursor; a raw material gel mixture preparation step of adding at least a seed crystal to obtain a raw material gel mixture; and a hydrothermal synthesis step of performing hydrothermal synthesis of the raw material gel mixture. Here, the zeolite obtained by the method for producing zeolite according to one aspect satisfies SiO2 / Al2O3 ≤ 13, and the seed crystal is a zeolite that has undergone de-Al treatment. In this context, "de-Al" refers to removing Al from within the zeolite framework and is not necessarily limited to releasing Al outside the bulk of the zeolite.

[0027] Zeolite refers to a zeolite as defined by the International Zeolite Association (IZA), preferably an aluminosilicate zeolite. Aluminosilicate zeolite contains at least oxygen (O), aluminum (Al), and silicon (Si) as atoms that constitute its skeletal structure.

[0028] The SiO₂ / Al₂O₃ ratio (molar ratio) of the zeolite obtained by the production method according to one aspect of the present disclosure is preferably 13 or less, more preferably 12.5 or less, still more preferably 12, and particularly preferably 11.5 or less. While the SiO₂ / Al₂O₃ molar ratio is not particularly limited, it is preferably 5 or more, more preferably 7 or more, still more preferably 8 or more, and particularly preferably 8.5 or more. By setting the SiO₂ / Al₂O₃ molar ratio of the obtained zeolite to 13 or less, a larger amount of transition metals and the like serving as active sites can be incorporated, and accordingly, the zeolite is expected to exhibit high activity when used as a catalyst. In addition, by setting the SiO₂ / Al₂O₃ ratio (molar ratio) to 5 or more, it is possible to prevent a decrease in the water durability of the zeolite caused by an excessively high Al content. As a result, a zeolite that can be used for catalysts, adsorbents, and the like can be obtained.

[0029] The contents of Si and Al in the zeolite of the present disclosure can usually be measured by ICP elemental analysis or X-ray fluorescence analysis. In X-ray fluorescence analysis, a calibration curve is created between the X-ray fluorescence intensity of the analysis element in a standard sample and the atomic concentration of the analysis element, and the contents of silicon atoms and aluminum in the zeolite sample can be determined by the X-ray fluorescence analysis method (XRF) using this calibration curve.

[0030] The method for producing a zeolite according to one aspect can produce a zeolite with a high Al content while using seed crystals that have undergone dealumination treatment. The inventors of the present disclosure have found that by using a zeolite subjected to dealumination treatment as a seed crystal, a large number of crystal nuclei can be rapidly generated in the zeolite raw material, and as a result, a small-particle-diameter zeolite with a high Al content can be produced with good yield.

[0031] (Mixing Step) In the mixing step, a Si element source, an Al element source, an alkali metal element source, and water are mixed to obtain an aqueous reactant precursor.

[0032] <Si Element Source> The Si element source is a compound having a Si atom (hereinafter sometimes referred to as "Si compound"). In the hydrothermal synthesis step, an amorphous Si compound is preferred because it is easily soluble and inexpensive so as to achieve a Si / Al ratio (molar ratio) suitable for zeolite crystallization. As the amorphous Si compound, amorphous silica such as colloidal silica, amorphous silica, fumed silica, and sodium silicate; trimethylethoxysilane, tetraethyl orthosilicate, aluminosilicate gel and the like can be used. These may be used alone, or two or more thereof may be used in any combination at any ratio. Further, from the viewpoints of easy uniform mixing with other raw materials and easy dissolution in water, colloidal silica, trimethylethoxysilane, tetraethyl orthosilicate, and aluminosilicate gel are preferred. Among the above, colloidal silica is particularly most preferred as the Si element source.

[0033] <Al element source> The Al element source is a compound containing an Al atom (hereinafter sometimes referred to as "Al compound"). As the Al compound, a compound that is easily soluble in water is preferred. Further, a compound that is well miscible with the Si compound and easily soluble so as to achieve a Si / Al ratio (molar ratio) suitable for zeolite crystallization in the aging step, the raw material gel mixture preparation step, and the hydrothermal synthesis step is preferred. From the above viewpoints, preferred examples of the Al compound include amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudoboehmite, aluminum alkoxide and the like. These may be used alone, or two or more thereof may be used in any combination at any ratio. Among these, amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a bayerite structure are particularly preferred. As the Al compound, it is preferable to use an amorphous aluminum element raw material, and among the above, amorphous aluminum hydroxide is particularly preferred.

[0034] (Ratio of Si element source to Al element source) The Si and Al sources must be blended such that the molar ratio of the Si source oxide to the Al source oxide (the molar ratio of SiO2 / Al2O3) in the raw material gel mixture described later is within the range of 5 to 1000. By blending the Si and Al element sources with the raw material gel mixture so that the molar ratio of SiO2 / Al2O3 is within the above-mentioned range, it becomes easier to obtain the desired zeolite. From the viewpoint of making it easier to obtain the target zeolite, the molar ratio of SiO2 / Al2O3 in the raw material gel mixture is more preferably 8 to 500, even more preferably 10 to 100, and particularly preferably 12 to 50.

[0035] <Sources of Alkali Metal Elements> The alkali metal element source is not particularly limited, and any compound containing alkali metal atoms may be used. Preferably, alkali metal ions are included in the aqueous reactant precursor before hydrothermal synthesis. As alkali metal element sources, the above-mentioned alkali metal atoms can be used as hydroxides, oxides, sulfates, nitrates, phosphates, chlorides, bromides, or other inorganic acid salts, as well as acetates, oxalates, citrates, or other organic acid salts. One alkali metal element source may be used alone, or two or more may be used in any ratio or combination. Known alkali metal elements used in the synthesis of zeolites can be used as alkali metal elements. Specifically, it is preferable that at least one is selected from lithium, sodium, potassium, rubidium, and cesium. The inclusion of these alkali metal elements facilitates the crystallization of zeolites and can also reduce the amount of expensive OSDA added. Among the alkali metal elements mentioned above, sodium and potassium are particularly preferred, and it is preferable to include at least a potassium element source. Furthermore, one alkali metal element may be used alone, or two or more may be used in combination.

[0036] (Amount of alkali metal elements mixed) The ratio of Si element source to alkali metal element source contained in the aqueous reactant precursor before hydrothermal synthesis is preferably 0.01 to 0.5 in molar ratio of M(2 / n)O (where M represents an alkali metal element and n is 1) to Si element oxide (M(2 / n)O / SiO2 molar ratio). Within this range, it is easier to obtain the desired zeolite. From the above viewpoint, it is even more preferable that the ratio of alkali metal element oxide to Si element oxide (M(2 / n)O / SiO2 molar ratio) is in the range of 0.02 to 0.5. Furthermore, the molar ratio of alkali metal element to Al atom contained in the aqueous reactant precursor is preferably 0.8 to 1.2. Furthermore, when mixing several types of alkali metal elements, a mixture of sodium and potassium elements is preferred. In this disclosure, it is particularly preferable that the alkali metal elements include at least potassium. In addition, the molar ratio of potassium to alkali metal elements contained in the alkali metal element source before the mixing step is preferably 20% or more and 40% or less, and more preferably 20% or more and 30% or less.

[0037] <Alkaline Earth Metal Element Sources> In the manufacturing method of this disclosure, an alkaline earth metal element source may be further mixed in addition to the alkali metal source. Examples of alkaline earth metal elements include beryllium, magnesium, calcium, strontium, and barium. As sources of alkaline earth metal elements, the following can be used: hydroxides, oxides, sulfates, nitrates, phosphates, inorganic acid salts such as chlorides and bromides of the above-mentioned alkaline earth metal elements, and organic acid salts such as acetates, oxalates, and citrates. The alkaline earth metal element raw materials may be used individually or in any combination of two or more in any ratio.

[0038] (Mixing amount of alkali metal element source and alkaline earth metal element source) The ratio of the Si element source to the alkali metal element source and alkaline earth metal element source contained in the aqueous reactant precursor is preferably 0.02 to 0.5 in terms of the molar ratio of M(2 / n)O to the oxide of the Si element source (M(2 / n)O / SiO2 molar ratio). Here, M represents an alkali metal element and an alkaline earth metal element, and n is 1 for alkali metals and 2 for alkaline earth metals. That is, the total amount of the alkali metal element source and the alkaline earth metal element source (hereinafter sometimes referred to as "alkali") is preferably 0.02 to 0.5 in terms of the molar ratio to the oxide of the Si element source. When the alkali amount is within the above range, it is easier to obtain the desired zeolite. From the above viewpoint, it is even more preferable that the alkali amount is in the range of 0.05 to 0.4.

[0039] (Amount of water added) The aqueous reactant precursor according to this disclosure contains water (H2O) as an essential component. The amount of water added is usually 5 or more, preferably 7 or more, in terms of molar ratio to Si atoms contained in the raw material gel mixture before hydrothermal synthesis, from the viewpoint of mitigating heat and raw material unevenness in the reactor and creating an environment where zeolite can easily crystallize. Furthermore, from the viewpoint of reducing the amount of waste liquid to be treated, improving one-batch efficiency (amount of zeolite recovered per reactor cycle), and enabling low-cost production by shortening the synthesis time, the amount of water added is usually 50 or less, preferably 40 or less, more preferably 30 or less, and even more preferably 25 or less, in terms of molar ratio to Si atoms contained in the raw material before hydrothermal synthesis, with 20 or less being particularly preferred. Note that water may be added in stages from the mixing step to obtain the aqueous reactant precursor to the raw material gel mixture preparation step, or it may be added all at once in any of the steps of the mixing step, the maturation step, and the raw material gel mixture preparation step.

[0040] The aqueous reactant precursor obtained in the mixing step is prepared by mixing an alkali metal element source, a Si element source, an Al element source, and water. The synthesis of the aqueous reactant precursor in the mixing step is preferably carried out in a stirred tank reactor equipped with a stirrer, such as a rotary stirrer with a scale of 800 g or more.

[0041] In the mixing process, the effects of this disclosure are significantly obtained when the total amount of materials mixed during the mixing of the Si element source, etc., is 800g or more, more preferably 2kg or more, even more preferably 10kg or more, and even more preferably 40kg or more. There is no particular upper limit, but considering the efficiency of extraction, 1000kg or less is preferred, and 500kg or less is more preferred. Furthermore, the effects are also significantly obtained when the size of the stirring tank during mixing is 1 liter or more, more preferably 2 liters or more, so it is preferable to use such a container. There is no particular upper limit, but it is usually 1000 liters or less, preferably 500 liters or less, and more preferably 200 liters or less.

[0042] When mixing the aqueous reactant precursors, there are no particular limitations on the procedure for adding each raw material, but from the viewpoint of easily controlling the viscosity change during mixing, it is preferable to add water containing an alkali metal element source to the Si element source and Al element source.

[0043] In the mixing process, the mixing conditions for the aforementioned Si source, Al source, alkali metal source, and water are not particularly limited. However, from the viewpoint of easily preparing a uniform raw material precursor, the average peripheral speed of the stirring blades of the stirring system is preferably 2 m / s or more, more preferably 7 m / s or more, and particularly preferably 10 m / s or more. On the other hand, from the viewpoint of low load on the drive unit in the system design and suppression of liquid splashing, it is preferably 30 m / s or less, more preferably 27 m / s or less, and particularly preferably 25 m / s or less.

[0044] The peripheral speed of the stirring blade used in the mixing process can be calculated using the following procedure. Peripheral speed (m / s) = π × diameter of the impeller (m) × (rotational speed) × (1 / 60) The peripheral speed does not necessarily have to be constant and may change continuously. In such cases, for example, when stirring is performed for a constant stirring time a under a peripheral speed A, and then again for a constant stirring time b under a peripheral speed B, the peripheral speed calculated by the following formula is defined as the average peripheral speed. That is, the average peripheral speed is the value obtained by dividing the product of the peripheral speed and stirring time at each peripheral speed by the sum of the stirring times. Average peripheral speed (m / s) = (Peripheral speed A × a + Peripheral speed B × b + ... + Peripheral speed N × n) / Sum of stirring time (a + b + ... + n) In this disclosure, stirring may be continued in the subsequent maturation step to prevent sedimentation and to make the mixing more uniform. Therefore, the mixing step may be considered to be the time during which the Si element source, Al element source, alkali metal element source, and water are stirred at the aforementioned preferred peripheral speed, for example, a peripheral speed of 2 m or more, and this continues within the aforementioned preferred mixing time range.

[0045] The viscosity and yield stress of the aqueous reactant precursor under room temperature conditions are not particularly limited, but from the viewpoint of facilitating the preparation of a uniform raw material gel mixture, the average viscosity of the aqueous reactant precursor is preferably 5 da·s or less, more preferably 1 dPa·s or less, and even more preferably 0.65 dPa·s or less. Similarly, for the same reason, the yield stress of the aqueous reactant precursor is preferably 100 Pa or less, more preferably 75 Pa or less, and even more preferably 50 Pa or less. On the other hand, from the viewpoint of solid yield, wastewater treatment, crystallization time, and substrate concentration, the average viscosity of the aqueous reactant precursor is preferably 0.01 dPa·s or higher, more preferably 0.1 dPa·s or higher, and even more preferably 0.3 dPa·s or higher. Also, for similar reasons, the yield stress is preferably 1 Pa or higher, more preferably 10 Pa or higher, and even more preferably 30 Pa or higher.

[0046] While there are no particular limitations on the mixing time, longer mixing times are preferable from the viewpoint of purity and uniformity. On the other hand, shorter mixing times are preferable from the viewpoint of manufacturing efficiency. Therefore, a mixing time of 30 seconds or more is preferable, and 60 seconds or more is particularly preferable. On the other hand, 7200 seconds or less is preferable, 1800 seconds or less is even more preferable, and 600 seconds or less is particularly preferable.

[0047] <Aging process> A manufacturing method according to one aspect of this disclosure includes a maturation step for maturing the aqueous reactant precursor obtained in the mixing step. The maturation step is preferably carried out in a stirred tank reactor in which the hydrothermal synthesis step was performed. (Aging process conditions) While there is no specific temperature requirement during the maturation process, the aqueous reaction precursor is preferably matured at a temperature of 140°C or lower, more preferably 120°C or lower, and most preferably 100°C or lower, in order to avoid the formation of poorly soluble crystalline precursors. The temperature may be kept constant during maturation, or it may be changed gradually or continuously.

[0048] (Aging time) The maturation time is not particularly limited. A short maturation time is preferable in terms of manufacturing efficiency, but a longer maturation time is preferable in terms of purity and uniformity. Specifically, maturation is preferably 15 minutes or more, more preferably 30 minutes or more, and particularly preferably 60 minutes or more. On the other hand, 36 hours or less is preferable, more preferably 24 hours or less, and particularly preferably 12 hours or less. Since maturation can be carried out with simple equipment, it is preferable to carry it out without external pressure. Furthermore, maturation is preferable to carry out while stirring in order to make the raw materials more uniform. The stirring method is not particularly limited.

[0049] <Preparation process of raw material gel mixture> In the raw material gel mixture preparation step, at least seed crystals are added to obtain the raw material gel mixture (sometimes simply called raw material gel) before hydrothermal synthesis. Because the amount of these mixtures is relatively small and the hydrothermal synthesis step follows immediately, uniform mixing is relatively easy. The raw material gel mixture preferably contains an aqueous reactant precursor that has undergone a maturation process and at least a seed crystal, and also contains other synthetic raw materials. In the raw material gel mixture preparation process, other synthetic raw materials may be added to the raw material gel mixture.

[0050] <Seed crystal> In a manufacturing method according to one aspect of this disclosure, a seed crystal is mixed with an aqueous reactant precursor in the zeolite raw material gel mixture preparation step. The seed crystal is a zeolite that has undergone aluminum removal treatment. The seed crystal before the Al removal treatment is a zeolite obtained by maturing the aforementioned aqueous reactant precursor (also called a precursor gel), mixing it with an organic structure-determining agent (OSDA) to obtain a raw material gel mixture, and then carrying out a hydrothermal synthesis reaction and calcining. It is manufactured by the same method as the manufacturing method according to one aspect of this disclosure, except that the Al removal treatment is performed.

[0051] The de-algae treatment of seed crystals is preferably carried out by treatment methods such as acid treatment, heat treatment, hydrothermal treatment, and steam treatment, with acid treatment and heat treatment being more preferable, and acid treatment being even more preferable. Acid treatment is preferably carried out using an inorganic acid such as nitric acid, hydrochloric acid, or sulfuric acid. Acid treatment with nitric acid is particularly preferred from the viewpoint of preventing pipe corrosion due to calcination treatment after acid treatment, and from the viewpoint of preventing impurity components from remaining in the pores and on the outer surface of the zeolite. Acid treatment can reduce the amount of acid derived from aluminum contained in the zeolite skeleton, which is the seed crystal. A manufacturing method according to one aspect of this disclosure can obtain a seed crystal with improved solubility in the raw material gel mixture by reducing the amount of acid derived from aluminum contained in the zeolite skeleton used as the seed crystal. By using such a seed crystal, it is possible to produce zeolite with a high Al content with good yield.

[0052] The de-alkaline treatment of seed crystals by acid treatment is preferably carried out using an aqueous solution of inorganic acid with a concentration of 0.01 to 10 M (mol / L), more preferably 0.03 to 5 M (mol / L), even more preferably 0.05 to 3 M (mol / L), and particularly preferably 0.1 to 2 M (mol / L). Using an aqueous solution of inorganic acid with a concentration of 10 M (mol / L) or less for the acid treatment prevents corrosion of the reaction vessel during production and prevents the zeolite crystal from collapsing due to excessive de-alkaline treatment. Using an aqueous solution of inorganic acid with a concentration of 0.01 M (mol / L) or more for the acid treatment can provide a sufficient de-alkaline effect. The de-alkaline treatment of seed crystals by acid treatment is preferably carried out under conditions above the freezing point but below the boiling point of an inorganic acid aqueous solution, more preferably 0 to 100°C, even more preferably 5 to 95°C, and particularly preferably 10 to 90°C. By performing the acid treatment at 0°C or above with an inorganic acid aqueous solution, a sufficient de-alkaline effect can be obtained. By performing the acid treatment at 100°C or below with an inorganic acid aqueous solution, it is possible to prevent the energy cost required for heating from becoming too high. Furthermore, it is possible to prevent the zeolite crystal from collapsing due to excessive de-alkaline treatment. The de-aluminization treatment of seed crystals by acid treatment is preferably carried out with stirring for 0.01 to 24 hours, more preferably 0.03 to 12 hours, even more preferably 0.05 to 6 hours, and particularly preferably 0.1 to 3 hours. By setting the de-aluminization treatment time of seed crystals by acid treatment to 0.01 hours or more, a sufficient de-aluminization effect can be obtained. Furthermore, even in large-scale production, it is possible to prevent the treatment from becoming difficult to perform with good reproducibility due to a time that is too short. In addition, by setting the de-aluminization treatment time of seed crystals by acid treatment to 24 hours or less, it is possible to prevent the energy cost required for heating from becoming too high and to prevent the zeolite crystal from collapsing due to excessive de-aluminization. The de-aluminized seed crystals can be dried and then used in the process of preparing the zeolite raw material gel mixture.

[0053] The de-algae treated seed crystals preferably have an acid content of 0.1 mmol / g or more and 1.6 mmol / g or less, more preferably 0.2 mmol / g or more and 1.2 mmol / g or less, and even more preferably 0.25 mmol / g or more and 0.8 mmol / g or less. By making the acid content of the seed crystal 0.1 mmol / g or more, the Al content of the zeolite is reduced, and the crystal nuclei formed when used as seed crystals dissolve rapidly and decompose into low molecular weight silane oligomers or aluminosilicate oligomers, which prevents the crystallization promotion effect from being lost. Furthermore, zeolites obtained by making the acid content of the seed crystal 1.6 mmol / g or less contain a lot of Al, and when used as seed crystals, their solubility does not become too low, and when used as seed crystals, a large amount of crystal nuclei can be generated, resulting in a sufficient crystal growth promotion effect. Zeolites with an acid content within the above range, when used as seed crystals, generate many crystal nuclei in the raw material gel, resulting in a high crystal growth promoting effect. Furthermore, the generation of a large number of crystal nuclei suppresses the growth of each individual nucleus, resulting in crystals with smaller particle sizes and higher surface areas, which are expected to be suitable for use as catalysts and the like.

[0054] The acid content of the seed crystal can be measured using NH3-TPD after protonating the Al sites in the zeolite framework. Methods for protonating Al sites in the zeolite skeleton include direct ion exchange with protons through acid treatment, and NH4 + This process may involve ion exchange to produce NH4-type zeolite, followed by calcination at over 500°C for more than one hour to remove NH3.

[0055] The de-aluminized seed crystals preferably have an average particle size of 500 nm or less, more preferably 485 nm or less, even more preferably 470 nm or less, and particularly preferably 460 nm or less. Furthermore, the average particle size of the de-aluminized seed crystals preferably has a particle size of 10 nm or more, more preferably 20 nm or more, even more preferably 40 nm or more, and particularly preferably 80 nm or more. By making the average particle size of the de-aluminized seed crystals 500 nm or less, the solubility of the zeolite can be increased, thereby increasing the amount of crystal nuclei generated when used as seed crystals. Therefore, a sufficient crystal growth promoting effect can be obtained from the seed crystals. By making the average particle size of the de-aluminized seed crystals 10 nm or more, it is possible to prevent the solubility from becoming too high when used as seed crystals, thereby preventing the generated crystal nuclei from rapidly dissolving and decomposing into low molecular weight silane oligomers or aluminosilicate oligomers. Therefore, a sufficient crystal growth promoting effect can be obtained from the seed crystals. Zeolites with an average particle size within the above range, when used as seed crystals, generate many crystal nuclei in the raw material gel, resulting in a high crystal growth promotion effect. Furthermore, the generation of a large number of crystal nuclei suppresses the growth of each individual nucleus, resulting in crystals with smaller particle sizes and higher surface areas, which are expected to be suitable for use as catalysts and the like.

[0056] The amount of seed crystal added to the raw material gel mixture is preferably 1% by mass or more relative to SiO2, assuming that all Si atoms contained in the raw material before hydrothermal synthesis are SiO2. Furthermore, to promote crystallization, it is preferably 2% by mass or more, particularly preferably 3% by mass or more, and most preferably 5% by mass or more. The seed crystal is a synthesized zeolite, and from the viewpoint of reducing manufacturing costs, it is preferably 20% by mass or less, and particularly preferably 10% by mass or less.

[0057] Furthermore, the seed crystal has a framework density of 14T / 1000Å. 3 The above is 19T / 1000Å. 3The following is preferable (hereinafter, this zeolite may be referred to as "the zeolite added in this disclosure"). Here, Framework density is the value described in ATLAS of zeoliteframe-worktypes Sixth revised Edition, 2007, ELSEVIER by CH. Baerlocher et al., and represents the framework density. That is, Framework density is the value per unit volume of zeolite 1000 Å. 3 This refers to the number of T atoms (atoms other than oxygen atoms that constitute the zeolite's skeletal structure) present around the zeolite, and this value is determined by the zeolite's structure. Furthermore, it is desirable that the added seed crystal has a CBU (composite building unit) common to the target zeolite. A CBU is formed by the linking of TO4 units and is a structural unit of zeolite. In this disclosure, the seed crystal of the zeolite to be added may be one type of zeolite used alone, or two or more types used in any ratio and combination. The seed crystal may be an uncalcined product that has not been calcined after hydrothermal synthesis, a calcined product that has been calcined after hydrothermal synthesis, or even an ion-exchanged product. Depending on the composition of the target zeolite (content, type, and water content of alkali metal atoms) and the synthesis environment (temperature, slurry pH), it is desirable to use an uncalcined product under conditions where calcined products are easily dissolved.

[0058] <Organic structure-determining agents (other synthetic raw materials)> In this disclosure, it is preferable that an organic structure-determining agent is included as another synthesis raw material in the raw material gel mixture before hydrothermal synthesis, and its content is preferably 0.01 or more and 1 or less in molar ratio to Si atoms. Furthermore, since the organic structure-determining agent is expensive among the synthesis raw materials, it is preferable to keep the amount used to a minimum. On the other hand, from the viewpoint of obtaining a high-purity target zeolite, it is preferable to include a certain amount or more of the organic structure-determining agent. From the above viewpoint, that is, in order to obtain a high-purity target zeolite while being inexpensive, the content of the organic structure-determining agent is more preferably 0.02 or more in molar ratio to Si atoms, even more preferably 0.05 or more, even more preferably 0.5 or less, even more preferably 0.3 or less, and particularly preferably 0.15 or less. Furthermore, when preparing the mixed raw materials for obtaining the aqueous reactant precursor, the organic structure-determining agent may be omitted or added in portions. The timing of adding the organic structure-determining agent is preferably when a portion of it is added during the raw material gel mixture preparation process, but is not particularly limited. Therefore, it is also possible to add it during the raw material gel mixture preparation process as another synthesis raw material.

[0059] <Hydrothermal synthesis process> In this manufacturing method, after maturation, a raw material gel mixture preparation step is performed to obtain a predetermined raw material composition, followed by a hydrothermal synthesis step. The target zeolite is synthesized by hydrothermal synthesis. Hydrothermal synthesis is usually carried out by placing the composition after zeolite addition into a pressure vessel and maintaining a predetermined temperature under self-generated pressure, stirring, rotating or oscillating the vessel, or in a static state. Hydrothermal synthesis is usually carried out at 140°C or higher. Furthermore, hydrothermal synthesis is usually carried out at 220°C or lower, preferably 200°C or lower, and more preferably 190°C or lower. The reaction time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and especially preferably 12 hours or more, while it is usually 14 days or less, preferably 7 days or less, more preferably 5 days or less, and even more preferably 2 days or less. The reaction temperature may be constant throughout the reaction, or it may be changed stepwise or continuously. The stirring speed may also be constant throughout the reaction, or it may be changed stepwise or continuously. Performing hydrothermal synthesis under the above conditions is preferable because it improves the yield of the target zeolite, reduces the generation of impurities, and lowers manufacturing costs.

[0060] A manufacturing method according to one aspect of the present disclosure produces a target zeolite by a manufacturing method comprising a mixing step for obtaining an aqueous reactant precursor, a raw material gel mixture preparation step, and a hydrothermal synthesis step. Here, it is preferable that the mixing step, the maturation step, the raw material gel mixture preparation step, and the hydrothermal synthesis step are carried out in the same stirred tank type reactor.

[0061] (Zeolite recovery) After hydrothermal synthesis, the zeolite is separated from the resulting composition (hydrothermal synthesis reaction solution). The obtained zeolite typically contains alkali metal atoms in its pores. If an organic structure-regulating agent is used, it typically contains the organic structure-regulating agent in its pores. Hereinafter, substances contained in the pores of hydrothermal-synthesized zeolite, such as organic structure-regulating agents and alkali metals, may be referred to as "structure-regulating agents, etc.," and zeolites containing these substances in their pores may be referred to as "SDA-containing zeolite." The method for separating SDA-containing zeolite from the hydrothermal synthesis reaction solution is not particularly limited, but typically includes filtration, decantation, or direct drying.

[0062] The zeolite containing SDA, etc., separated and recovered from the hydrothermal synthesis reaction solution may be washed with water, dried, and then calcined as appropriate to remove the structural restrictors used during production.

[0063] As a method for removing the structure-directing agent and the like from a zeolite containing SDA and the like, a liquid phase treatment using an acidic solution or a chemical solution containing a structure-directing agent decomposing component, an ion exchange treatment using a resin or the like, or a thermal decomposition treatment can be employed, and these treatments may be used in combination. The contained organic structure-directing agent and the like can be removed by a method such as extraction with an organic solvent such as an aqueous ethanol solution. On the other hand, from the viewpoint of productivity, removal of the organic structure-directing agent and the like by calcination is preferred. Usually, calcination is performed at a temperature of 300°C or higher and 1000°C or lower in an atmosphere of air, an oxygen-containing inert gas, or an inert gas. The calcination temperature is preferably 400°C or higher, more preferably 450°C or higher, still more preferably 500°C or higher, and is preferably 900°C or lower, more preferably 800°C or lower, still more preferably 700°C or lower. As the inert gas, nitrogen or the like can be used.

[0064] <Scope of Application of the Present Disclosure> The production method of the present disclosure can be applied to various zeolites. Specific particularly preferred zeolites include AEI-type zeolite, CHA-type zeolite, CON-type zeolite and the like. In addition, the zeolite obtained by the present disclosure preferably has a Framework density of 14T / 1000Å 3 or more and 19T / 1000Å 3 or less. In particular, the zeolite preferably has at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring. The production method of the present disclosure is suitably applied to zeolites that are difficult to produce among the above zeolites, and among these, it is preferably applied to zeolites that are particularly difficult to mass-produce. Among the above zeolites, AEI-type zeolite in particular is particularly susceptible to the influence of viscosity between small-scale and large-scale production. Therefore, the production method of the present disclosure is particularly effective in the production of AEI-type zeolite. Hereinafter, description will be given taking AEI-type zeolite, which is considered difficult to produce, as an example, but the production method of the present disclosure is not limited to these zeolites.

[0065] (AEI-type Zeolite) AEI-type zeolite is one example of a zeolite produced by the manufacturing method disclosed herein. In this specification, AEI-type zeolite will be used as an example in the examples described later. AEI-type zeolite will be described below. The AEI-type zeolite exemplified in the examples refers to one with an AEI structure as defined by the code for the skeletal structure of zeolites as defined by the International Zeolite Association (IZA). Its structure is characterized by X-ray diffraction data. However, when measuring a zeolite that has actually been produced, the intensity ratio and peak position of each peak will be slightly shifted due to the influence of the crystal plane growth direction of the zeolite, the ratio of constituent elements, adsorbed substances, and the presence of defects. Therefore, it is not possible to obtain values ​​that are exactly the same as the parameters of the AEI structure described in the IZA specifications, and a range of about 10% is acceptable. Major peaks observed in X-ray diffraction of AEI-type zeolites include, for example, when using CuKα radiation as the source, the 110-plane peak at 2θ = 9.5° ± 0.2°, the 022-plane peak at 16.9° ± 0.2°, and the 310-plane peak at 20.6° ± 0.2°.

[0066] One of the advantages of this manufacturing method is that it allows for the production of high-purity AEI-type zeolite on a large scale while reducing the amount of expensive organic structure-determining agents used.

[0067] The performance of the target AEI-type zeolite, such as catalytic activity, improves as its purity increases. Therefore, the purity of the target AEI-type zeolite is preferably 80% or higher, more preferably 85% or higher, and particularly preferably 90% or higher. Generally, the higher the purity of the target zeolite, the better, with an upper limit of 100%.

[0068] The purity of AEI-type zeolite can be calculated using the following procedure. First, the by-product content in the zeolite is calculated. The by-product content can be determined using the XRD pattern obtained from an XRD measurement with CuKα radiation as the source, and from the following equation (1).

[0069] By-product content (%) = I (peak intensity of by-product) / I (AEI-type zeolite + by-product) (Peak intensity of the product) × 100 ... (1)

[0070] In equation (1) above, I(AEI) is the intensity of the main peak of AEI. The main peak is the peak with the highest intensity among the XRD peaks that characterize each zeolite, and in AEI-type zeolites, it is typically the peak at 2θ = 9.5° ± 0.2°. I(byproduct) is the intensity of the main peak of the byproduct. I(byproduct) is the intensity of the XRD peak that characterizes the structure of the byproduct. For example, if the byproduct zeolite is MOR-type zeolite, I(byproduct) is the intensity of the XRD peak with its peak top at 2θ = 6.5 ± 0.1°. If the byproduct zeolite is GME-type zeolite, I(byproduct) is the intensity of the XRD peak with its peak top at 2θ = 7.5 ± 0.1°. If the byproduct zeolite is MER-type zeolite, I(byproduct) is the intensity of the XRD peak with its peak top at 2θ = 12.5 ± 0.1°. If the by-product zeolite is ANA-type zeolite, I (by-product) is the intensity of the XRD peak with its peak top at 2θ = 15.9 ± 0.1°. If the by-product is sanidine, I (by-product) is the intensity of the XRD peak with its peak top at 2θ = 21.7 ± 0.1°. If there are two or more by-products, I (by-product) is calculated by adding the peak intensities.

[0071] Based on the by-product content (%) calculated as described above, the purity of the AEI-type zeolite can be determined from the following equation (2). Purity of AEI-type zeolite (%) = 100 - By-product content (%) ... (2)

[0072] (Applications of AEI-type zeolite) The use of the zeolite produced by the production method according to one aspect of the present disclosure is not particularly limited, and it is suitably used as a catalyst, an adsorbent, a separation material, and the like. Above all, it is preferably used for catalysts and adsorbents. The AEI-type zeolite of the examples is particularly suitably used as a catalyst for exhaust gas purification of automobiles and the like. Further, the AEI-type zeolite is also suitably used as an adsorbent for exhaust gas purification of automobiles and the like.

[0073] The present disclosure is not limited to the above-described respective embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining technical means respectively disclosed in different embodiments are also included in the technical scope of the present disclosure. [Examples]

[0074] Hereinafter, the present disclosure will be specifically described with reference to Examples, but the present disclosure is not limited in any way by the following Examples as long as it does not exceed the gist thereof.

[0075] [Analysis and Evaluation] The analysis of the zeolites obtained in the following Examples and Comparative Examples was carried out by the following methods.

[0076] <Measurement of NH3-TPD> The total acid amount of the untreated seed crystal and the acid-treated seed crystal and the acid amount derived from Al in the zeolite framework were determined by the ammonia temperature-programmed desorption (NH3-TPD) method of zeolite as follows. For the seed crystals not subjected to acid treatment, ion exchange to H-form was performed before NH3-TPD measurement. About 50 mg of zeolite powder was filled in a quartz glass cell, and the measurement was performed under the following conditions.

[0077] [Table 1]

[0078] The total acid amount of the zeolite measured in the range of 100 to 600°C was defined as follows. Total acid amount of zeolite = NH3 desorption amount / Weight of the filled dry zeolite powder Furthermore, the weight of the dried zeolite powder was calculated using the following formula. Weight of dry zeolite powder = Weight of filled zeolite powder × (100 - Moisture content (%)) / 100 Here, the thermogravimetric change from room temperature to 200°C was measured under air circulation, and the moisture content was determined using the following formula. Moisture content (%) = Weight change / Sample volume × 100 The amount of acid derived from the Al skeleton was determined using the following formula. Amount of acid derived from the Al skeleton = (Waveform area at 300-600°C / Waveform area at 100-600°C) × Total amount of acid

[0079] <Measurement using powder XRD> (Sample preparation) 100 mg of zeolite samples, manually ground using an agate mortar, were placed in sample holders of the same shape to ensure a consistent sample volume. (Equipment specifications and measurement conditions) The specifications and measurement conditions for the powder XRD analyzer are as follows:

[0080] [Table 2]

[0081] (Purity of AEI-type zeolite) Using the following equations (1) and (2), the purity of the AEI-type zeolite was determined from the intensity of the main peak of the AEI-type zeolite and the intensity of the main peaks of each by-product in the XRD pattern obtained by XRD measurement. However, since XRD patterns contain background noise, peaks with an intensity of 40 or less were excluded as background noise. By-product content (%) = I(peak intensity of by-product) / I(peak intensity of AEI-type zeolite + by-product) × 100 ... (1) Purity of AEI-type zeolite (%) = 100 - By-product content (%) ... (2)

[0082] <Elemental analysis> A zeolite sample serving as a standard sample was heated and dissolved in an aqueous alkali solution and an aqueous hydrofluoric acid solution, and then the Si / Al ratio and Cu / Al ratio were determined by inductively coupled plasma (ICP: Inductively Coupled Plasma) emission spectroscopic analysis. Subsequently, a calibration curve was prepared between the fluorescent X-ray intensity of the analytical element in the standard sample and the atomic concentration of the analytical element. Using this calibration curve, the zeolites obtained in each Example were analyzed by fluorescent X-ray analysis (XRF) to determine their Si / Al ratio. The ICP analysis was performed using an apparatus manufactured by Thermo Fisher Scientific, model name: iCAP7600 Duo. XRF was performed using a wavelength-dispersive compact fluorescent X-ray analyzer manufactured by Rigaku Corporation: Supermini200. By this method, elemental ratios such as the Si / Al ratio and Cu / Al ratio in the zeolite framework were determined.

[0083] <FT-IR Measurement> The specifications and measurement conditions for FT-IR are as follows.

[0084] [Table 3]

[0085] <Evaluation of Catalytic Activity> Each of the catalyst samples before and after steam treatment was press-molded, then crushed and sieved to adjust the particle size to 0.6 to 1 mm. 1 mL of the sized catalyst sample was packed into an atmospheric pressure fixed-bed flow-type reaction tube. The catalyst layer was heated while a gas having the composition described in Table 4 below was passed through the catalyst layer at a space velocity SV of 200000 / h. At each temperature of 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, and 500°C, the outlet NOx (NO + NO2) concentration was measured with a NOx meter, and when the outlet NOx concentration became constant, the NOx conversion rate was calculated by the following formula. NOx Conversion Rate (%) ={(Inlet NOx Concentration) - (Outlet NOx Concentration)} / (Inlet NOx Concentration) × 100 Further, the IR spectrum of the outlet gas was measured using FT-IR, and the N2O emission amount of the catalyst sample was calculated by the calibration curve method. From the calculated N2O emission amount, N2O selectivity was calculated by the following formula. N2O Selectivity (%) =100(%)×Generated N2O (ppm) / (NOx conversion rate×Inlet NOx) (ppm)

[0086] The performance of the catalyst before and after steam treatment was evaluated based on the calculated NOx conversion rate at each temperature, N2O emission amount, and the average value of selectivity.

[0087]

Table 4

[0088] [Synthesis Example 1] <Synthesis of zeolite for seed crystal> The procedure was carried out in the same manner as in Example 4 of Japanese Unexamined Patent Publication No. 2025-10071, to obtain zeolite powder. When XRD measurement was performed on the obtained zeolite powder, it was confirmed to be AEI-type zeolite. The XRD chart of this zeolite powder is shown in Figure 1, and the SEM image is shown in Figure 2. The SiO2 / Al2O3 ratio (molar ratio) of the obtained AEI-type zeolite by XRF analysis was 9.2.

[0089] Figure 2 is an SEM image taken at a magnification of 5000 times of the AEI-type zeolite synthesized for seed crystals. 75 arbitrary primary particles were selected from the SEM image of the AEI-type zeolite, and the average primary particle diameter obtained by arithmetically averaging the respective particle diameters was 446 nm as shown in Table 5.

[0090] <Calcination of zeolite for seed crystal> To remove organic substances in the zeolite, the synthesized AEI zeolite powder was calcined for 6 hours under an air stream at 600°C, to obtain Seed Crystal 1.

[0091] <Conversion to H-form> Next, to determine the amount of Al from the amount of acid in the zeolite skeleton of seed crystal 1, it was converted to the H type. A zeolite dispersion was prepared from the calcined zeolite and a 2.7 M NH4NO3 aqueous solution such that the slurry concentration calculated by the following formula was 14% by weight. Slurry concentration = Amount of zeolite powder (g) / (Amount of zeolite powder (g) + Amount of NH4NO3 aqueous solution (g)) × 100 (weight %) Ion exchange was performed by stirring the zeolite dispersion at 80°C for 1 hour. The zeolite was recovered by filtration and washed three times with deionized water. Subsequently, the ion exchange and three washing steps described above were repeated one more time. The resulting zeolite powder was dried at 100°C for 12 hours to obtain NH4-type AEI zeolite. To remove NH3 from the zeolite and convert it to the H-type, the obtained NH4-type AEI zeolite was calcined at 500°C under an air stream for 2 hours to obtain H-type seed crystal 1.

[0092] <Seed crystal acid amount measurement> The acid content of the obtained H-type seed crystal 1 was measured using NH3-TPD and found to be 1.85 mmol / g. Seed crystal 1 before acid treatment was used as the seed crystal for zeolite synthesis in Comparative Example 1.

[0093] [Example 1] <Acid treatment of seed crystals> 80 ml of 1.0 M HNO3 aqueous solution was mixed with 320 ml of water to prepare 400 ml of 0.2 M HNO3 aqueous solution. 20 g of seed crystal 1 was added to the resulting HNO3 aqueous solution to prepare a slurry. The resulting slurry was heated and stirred at 50°C for 6 hours. The solid content was recovered from the resulting slurry by filtration and washing to obtain zeolite powder. Seed crystal 2 was obtained by drying the obtained zeolite powder at 100°C for 12 hours. Seed crystal 2, after acid treatment, was used as the seed crystal for zeolite synthesis in Example 1.

[0094] <Measurement of acid content in seed crystals> The acid content of the obtained seed crystal 2 was measured using NH3-TPD and found to be 0.36 mmol / g.

[0095] <Preparation of aqueous reactant precursor (precursor gel)> 313.4 g of water and 43.3 g of amorphous Al(OH)3 (Al2O3, 54.3 wt%, manufactured by Kyowa Chemical Industry) were added, to which 446.1 g of Snowtex 40 (silica concentration: 40 wt%, manufactured by Nissan Chemical) was added, and the mixture was stirred at 300 rpm for 1 hour at room temperature to prepare slurry A-1. Next, aqueous solution B-1 was prepared by dissolving 19.8 g of KOH (manufactured by Kishida Chemical, 85 wt%) and 34.1 g of NaOH (manufactured by Kishida Chemical, 97 wt%) in 100 g of water. Next, aqueous solution B-1 was added to slurry A-1 and stirred in a mixer at 5000 rpm for 3 minutes to prepare a precursor gel. At this time, 130 g of additional water (H2O) was added for washing, and the mixture was designated as precursor gel C-1. The obtained precursor gel C-1 was heated to 80°C at 240 rpm over 2 hours, and then aged for 4 hours. After that, it was allowed to cool naturally to room temperature.

[0096] <Preparation of raw material gel mixture (raw material gel)> To precursor gel C-1, 135.7 g of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure-determining agent (OSDA), and the mixture was stirred at room temperature at 240 rpm for 0.5 hours. Subsequently, 18 g of seed crystal 2 powder was mixed with 30 g of water (H2O) to prepare a slurry. This slurry was added to precursor gel C-1, and the mixture was stirred at room temperature at 240 rpm for 0.5 hours to obtain the raw material gel. The molar composition ratios of the raw material gel mixture before hydrothermal synthesis, excluding the seed crystal, are shown below, with SiO2 set to 1. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0097] <Hydrothermal synthesis of zeolites> The raw material gel prepared by the above method was placed in a stirred-tank reactor and heated to 180°C over 25.55 hours while stirring at 120 rpm, and then held for 12 hours to perform hydrothermal synthesis. At this time, as the stirring tank type reactor, a stirring blade equipped with Maxblend (registered trademark) impeller and two baffles was used. After the hydrothermal synthesis reaction, the reaction solution was cooled, and the generated crystals were recovered by filtration. The recovered crystals were dried at 100°C for 12 hours to obtain zeolite powder 1. When the XRD of the obtained zeolite powder 1 was measured, it was confirmed to be an AEI-type zeolite. The synthesis conditions of this zeolite powder 1 are shown in Table 6, the XRD chart is shown in Figure 3, and the SEM image is shown in Figure 4. The SiO₂ / Al₂O₃ ratio (molar ratio) of the obtained AEI-type zeolite measured by XRF analysis was 9.1.

[0098] <Purity> Regarding the obtained AEI-type zeolite, the peak intensities of the target product and impurities obtained from the XRD chart (Figure 4) are shown in Table 7. As shown in Table 8, the purity of the AEI-type zeolite contained in zeolite powder 1 was 100%.

[0099] <Particle Size> For the obtained AEI-type zeolite, 76 arbitrary primary particles were selected from the SEM image (Figure 4) taken at a magnification of 20000 times, and the average primary particle diameter obtained by arithmetically averaging the respective particle diameters was 250 nm as shown in Table 9.

[0100] <Calcination of Zeolite> In order to remove organic substances in the zeolite, the synthesized zeolite powder 1 was calcined for 6 hours under an air stream at 600°C.

[0101] <Conversion to H-form> Next, in order to remove Na ions in the calcined zeolite powder 1, a zeolite dispersion liquid was prepared from the calcined zeolite and a 2.7 M NH₄NO₃ aqueous solution such that the slurry concentration calculated by the following formula was 14% by weight. Slurry concentration = Amount of zeolite powder (g) / (Amount of zeolite powder (g) + Amount of NH₄NO₃ aqueous solution (g)) × 100 (% by weight) Ion exchange was performed by stirring the zeolite dispersion at 80°C for 1 hour. The zeolite was recovered by filtration and washed 3 times with ion-exchanged water. Thereafter, the aforementioned ion exchange and 3 washes were repeated once more. The obtained zeolite powder was dried at 100°C for 12 hours to obtain NH4-type AEI zeolite. In order to remove NH3 from the zeolite and convert it to the H-form, the obtained NH4-type AEI zeolite was calcined under an air flow at 500°C for 2 hours to obtain H-type AEI zeolite.

[0102] <Preparation of Cu-containing Zeolite> Copper acetate (Cu(OAc)₂·H₂O, manufactured by Kishida Chemical Co., Ltd.) was dissolved in water to obtain a 0.05 M copper(II) acetate aqueous solution. A dispersion prepared by mixing this copper(II) acetate aqueous solution with H-type AEI zeolite powder at a weight ratio of 10:1 was stirred at room temperature for 2 hours to perform ion exchange. The zeolite was recovered by filtration and washed 3 times with ion-exchanged water. The obtained zeolite powder was dried at 100°C for 12 hours to obtain Cu-containing AEI zeolite. The Cu / Al ratio of the Cu-containing AEI zeolite as determined by XRF analysis was 0.19, and the Cu content was 3.3% by weight.

[0103] The physical properties and catalytic activity evaluations of the Cu-containing AEI zeolite catalyst of Example 1 are shown in Table 10 and Figure 5.

[0104] [Example 2] <Acid Treatment of Seed Crystal> 800 ml of water was added to 200 ml of 1.0 M HNO₃ aqueous solution to prepare 1000 ml of 0.2 M HNO₃ aqueous solution. 50 g of Seed Crystal 1 was added to the obtained HNO₃ aqueous solution to prepare a slurry. The resulting slurry was heated and stirred at 50°C for 6 hours. The solid content was recovered from the obtained slurry by filtration and washed to obtain a zeolite powder. The obtained zeolite powder was dried at 100°C for 12 hours. The above operation was performed 16 times to obtain a total of 798 g of zeolite powder (Seed Crystal 3). The obtained Seed Crystal 3 was used as the seed crystal for zeolite synthesis in Example 2.

[0105] <Acid content measurement> The acid content of the obtained seed crystal 3 was measured using NH3-TPD and found to be 0.37 mmol / g.

[0106] <Preparation of aqueous reactant precursor (precursor gel)> To prepare slurry A-3, 3474.4 g of amorphous Al(OH)3 (Al2O3, 53.5% by mass, manufactured by Kyoward Chemical) was added to 25800 g of water, and 35810.4 g of colloidal silica SiO2 (SiO2, 40.2% by mass, manufactured by Nissan Chemical) was added. To prepare transparent solution B-3, 2734.8 g of NaOH (manufactured by Fujifilm Wako Pure Chemical Industries), 1589.3 g of KOH (manufactured by Fujifilm Wako Pure Chemical Industries), and 12040 g of water were mixed and stirred to dissolve. Transparent solution B-3 was added to slurry A-3, and the mixture was stirred at room temperature for 12 min using a 150 L scale high-speed stirrer (average blade speed of 11 m / s) to obtain a precursor gel.

[0107] <Preparation of raw material gel mixture (raw material gel)> 39.0 kg of the prepared precursor gel was placed in a 100 L scale stirred-tank reactor, and then aged at 80°C for 6 hours while stirring at 120 rpm using a Maxblend blade (2 baffles). To the aged mixture, 5.22 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure-correcting agent (OSDA), and then washed with 1.13 kg of water. Finally, 0.69 kg of seed crystal 3 was swollen in 1.75 kg of water and then mixed, and stirred at room temperature for 30 minutes to obtain the starting gel. The molar composition ratios of the raw material gel mixtures other than the seed crystal are shown below, with SiO2 set to 1. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0108] <Hydrothermal synthesis of zeolites> The raw material gel prepared by the above method was subjected to hydrothermal synthesis for 20 hours while stirring at 90 rpm at a temperature of 180°C. At this time, Maxblend impellers were used in the stirred tank reactor, and two baffles were used. After the hydrothermal synthesis reaction, the reaction solution was cooled, and Powder 2 was recovered by filtration. The recovered Powder 2 was dried at 100°C for 12 hours. When XRD of the obtained Powder 2 was measured, it was confirmed that AEI-type zeolite was synthesized. The synthesis conditions of Powder 2 are shown in Table 6, the XRD chart is shown in Figure 6, and the SEM image is shown in Figure 7. The SiO2 / Al2O3 ratio (molar ratio) by XRF analysis was 8.9.

[0109] <Purity> Regarding the obtained AEI-type zeolite, the peak intensities of the target product and impurities obtained from the XRD chart (Figure 6) are shown in Table 7. The AEI purity was 86.4% as shown in Table 8.

[0110] <Particle Size> For the obtained AEI-type zeolite, 75 arbitrary primary particles were selected from the SEM image (Figure 7) taken at a magnification of 20000 times, and the average primary particle diameter obtained by arithmetically averaging each particle diameter was 283 nm as shown in Table 9.

[0111] <Calcination of Zeolite> The AEI zeolite obtained above was calcined in the same manner as in Example 1.

[0112] <Conversion to H-form> The calcined AEI zeolite was converted to H-form in the same manner as in Example 1.

[0113] <Preparation of Cu-Containing Zeolite> A Cu-containing zeolite was prepared from the obtained H-form AEI zeolite in the same manner as in Example 1. The Cu / Al of the Cu-containing AEI zeolite by XRF analysis was 0.22, and the Cu content was 3.9 wt%.

[0114] Regarding the Cu-containing AEI zeolite catalyst of Example 2, the physical properties are shown in Table 5, and the evaluation of catalyst activity is shown in Figure 8.

[0115] [Comparative Example 1] <Preparation of aqueous reactant precursor (precursor gel)> A precursor gel was obtained using the same procedure as in Example 1.

[0116] <Preparation of raw material gel mixture (raw material gel)> 78.0 kg of the prepared raw material gel was placed in a 100 L scale stirred-tank reactor, and then aged at 80°C for 6 hours while stirring at 120 rpm using a Maxblend blade (2 baffles). To the aged mixture, 5.22 kg of a 35.2% aqueous solution of N,N-dimethyl-3,5-dimethylpiperidinium hydroxide (manufactured by Seichem Co., Ltd.) was added as an organic structure-correcting agent (OSDA), and then washed with 2.35 kg of water. Finally, 1.38 kg of seed crystal 1 was swollen in 5.5 kg of water and then mixed, and stirred at room temperature for 30 minutes to obtain the precursor gel. The molar composition ratios of the raw material gel mixture, excluding the seed crystal, are shown below. SiO2:0.077Al2O3:0.3NaOH:0.1KOH:17.5H2O:0.1OSDA

[0117] <Hydrothermal synthesis of zeolites> The raw material gel prepared by the above method was subjected to hydrothermal synthesis for 24 hours at a temperature of 180°C while being stirred (120 rpm). At this time, a Maxblend blade was used in a stirred tank reactor with two baffles. After the hydrothermal synthesis reaction, the reaction solution was cooled and powder 3 was recovered by filtration. The recovered powder 2 was dried at 100°C for 12 hours. When the XRD of the obtained powder 3 was measured, the formation of AEI-type zeolite was confirmed. The synthesis conditions for powder 3 are shown in Table 6, the XRD chart in Figure 9, and the SEM image in Figure 10. The SiO2 / Al2O3 ratio (molar ratio) determined by XRF analysis was 8.7.

[0118] <Purity> Table 7 shows the peak intensities of the target substance and impurities obtained from the XRD chart (Figure 9) of the obtained AEI-type zeolite. The AEI purity was 66.6%, as shown in Table 8.

[0119] <Particle size> For the obtained AEI-type zeolite, 65 arbitrary primary particles were selected from SEM images taken at 5000x magnification (Figure 10), and the average primary particle diameter obtained by arithmetic mean-meaning the individual particle diameters was 714 nm, as shown in Table 9.

[0120] Table 5 below shows the physical properties of various crystals synthesized for use as Cu-containing AEI zeolite catalysts.

[0121] [Table 5]

[0122] Tables 6-1 to 6-3 below show the synthesis conditions for the AEI-type zeolite in Examples 1 and 2, and Comparative Example 1.

[0123] [Table 6-1] [Table 6-2] [Table 6-3]

[0124] Table 7 below shows the peak intensities of the target substance and impurities in AEI-type zeolite obtained from XRD charts. [Table 7]

[0125] Table 8 below shows the peak intensities of the target substance and impurities in the AEI-type zeolite of Examples 1 and 2 and Comparative Example 1.

[0126] [Table 8]

[0127] As shown in Tables 7 and 8, AEI-type zeolites using seed crystals treated with acid de-algae treatment contain no MOR compared to AEI-type zeolites using seed crystals that have not undergone de-algae treatment. Furthermore, the content of the by-product Sanidine is low, and the results show high purity of the target product.

[0128] Table 9 below shows the SiO2 / Al2O3 and average particle size of the AEI-type zeolite for Examples 1 and 2 and Comparative Example 1.

[0129] [Table 9]

[0130] As shown in Table 9, the AEI-type zeolites of Examples 1 and 2 have a lower average particle size than the AEI-type zeolite of Comparative Example 1. This suggests that in Examples 1 and 2, where seed crystals with reduced Al content due to acid treatment were used, many crystal nuclei were generated from the seed crystals during the zeolite synthesis process. As a result, the Si and Al sources in the raw material gel were rapidly consumed by the crystal growth of small-particle AEI crystals, suppressing the purification of the impurity phase and producing highly crystalline AEI-type zeolites. On the other hand, in Comparative Example 1, the seed crystal of the AEI-type zeolite had a high Al content and low solubility, resulting in fewer crystal nuclei being generated, a larger particle size per grain, and insufficient crystallization promotion effect. This likely resulted in the formation of AEI-type zeolites with low crystallinity and large particle size. Furthermore, it is believed that some of the Si and Al sources in the raw material gel were used to generate the impurity phase while the AEI crystals were growing, resulting in the generation of a large amount of impurity phase.

[0131] Table 10 shows the physical properties and catalytic activity evaluation results of the Cu-containing AEI zeolite catalysts of Examples 1 and 2.

[0132] [Table 10] [Industrial applicability]

[0133] A manufacturing method according to one aspect of this disclosure can be used, for example, to produce zeolites suitable for use as catalysts, adsorbents, separation materials, etc. Zeolites produced by the manufacturing method according to one aspect can be suitably used, for example, as catalysts for exhaust gas purification in automobiles, etc., and as adsorbents for exhaust gas purification in automobiles, etc.

Claims

1. A mixing step of mixing an elemental Si source, an elemental Al source, an alkali metal element source, and water to obtain an aqueous reactant precursor, A maturation step for maturing the aqueous reactant precursor, A raw material gel mixture preparation step involves adding at least seed crystals to obtain a raw material gel mixture, A method for producing zeolite, comprising a hydrothermal synthesis step for performing hydrothermal synthesis of the raw material gel mixture, The aforementioned zeolite is SiO 2 / Al 2 O 3 Satisfying ≤ 13, A method for producing zeolite, wherein the seed crystal is a zeolite that has undergone aluminum removal treatment.

2. The method for producing zeolite according to claim 1, wherein in the raw material gel mixture preparation step, an organic structure-determining agent is added to the raw material gel mixture.

3. The method for producing a zeolite according to claim 1, wherein the average particle size of the zeolite and the seed crystal is 500 nm or less.

4. The aforementioned seed crystal is SiO 2 / Al 2 O 3 A method for producing a zeolite according to claim 1, wherein the zeolite has a size of ≤13.

5. A method for producing a zeolite according to any one of claims 1 to 4, wherein the Al de-treatment of the seed crystal is an acid treatment.

6. The method for producing zeolite according to claim 5, wherein the amount of acid after acid treatment of the seed crystal is 0.1 mmol / g or more and 1.6 mmol / g or less.

7. The Framework density of the zeolite and the seed crystal is 14T / 1000Å. 3 The above is 19T / 1000Å. 3 The method for producing zeolite according to claim 1 is as follows:

8. The method for producing a zeolite according to claim 1, wherein the zeolite and the seed crystal have at least one of an 8-membered oxygen ring, a 10-membered oxygen ring, and a 12-membered oxygen ring.

Citation Information

Patent Citations

  • AEI zeolite and manufacturing method and application thereof

    JP2017081809A

  • Method for producing AEI type zeolite

    JP2017206417A

  • Production method of AEI zeolite, catalyst, and adsorbent

    JP2021147260A